Bilateral Alterations in Corneal Nerves, Dendritic Cells and Tear Cytokine Levels in Ocular Surface Disease - Yamaguchi, Takefumi (Cornea, 2016)
This review summarizes recent literature regarding corneal imaging in human subjects using in vivo confocal microscopy and corneal immune cells, nerves, and tear cytokine levels in ocular surface diseases as well as corneal immune privilege. The significance of interactions between corneal immune cells and nerves in health, neurotrophic keratopathy, and infectious keratitis are discussed. Furthermore, bilateral alterations of immune cells and nerves in clinically unilateral corneal diseases and the link to changes of tear cytokines or neuropeptide levels in contralateral eyes are described. Recent studies reported increased density and morphologic changes of corneal dendritic cells in ocular surface disease that correlated with a decrease in sub-basal nerve corneal nerves, suggesting potential interactions between the immune and nervous systems in the cornea. Although the relevance of tear cytokines is poorly understood, tear cytokines might have an important role in the pathogenesis of ocular surface diseases. In humans and experimental animal models, alterations in immune cells, cytokines and immunomodulatory neuropeptide levels in contralateral eyes might mediate the incidence of bilateral infectious keratitis and loss of immune privilege of the cornea in bilateral corneal transplantation or neurotrophic keratopathy cases. The discovery of bilateral alterations of immune cells and nerves in ocular surface diseases is considered the missing link between the immune and nervous systems in the cornea, and demonstrates how studies of animal models and human patients aid our understanding of human corneal disease phenomena.